Europe, China and the United States: Three different approaches to the development of offshore wind energy. (July 2019) - deCastro, M.; Salvador, S.; Gómez-Gesteira, M.; Costoya, X.; Carvalho, D.; Sanz-Larruga, F.J.; Gimeno, L.
Abstract: In those countries where wind plays a major role in the energy mix (EU, China and USA) actions have been carried out to develop offshore wind energy, albeit to varying degrees. These actions range from studying offshore wind to the development of laws and planning related to the construction of wind farms. Europe currently leads the way in offshore wind energy (with 84% of global installations), having achieved technical and commercial maturity, including the first floating wind farm to generate electricity, together with an emerging zero-subsidy culture. The Chinese wind industry has seen rapid development since 2005, however, well established laws, the use of a one-stop-shop system in the licencing process, and the establishment of higher feed-in tariffs (FITs), could all boost the Chinese offshore wind industry further. The possible future role of the USA in the offshore wind industry is now in the hands of its decision makers. A more streamlined licencing process, together with a long-term vision enshrined within stable economic incentives, could help to boost the offshore wind industry in the USA. Highlights: Analysis of offshore wind resources and regulations is key to the wind energy growth. European offshore wind industry has reached technological and commercial maturity. The EU, China, and the USA have all taken steps to develop offshore wind energy. The role of the USA in future offshore wind energy depends on its decision makers. China has entered a new and decisive phase in the offshore wind energy development.